Microsoft Office 2007 - Shelly, Gary B. (Thomson Course Technology, 2008)
Introduce your students to the new generation of Microsoft Office with the new generation of Shelly Cashman Series books! For the past three decades, the Shelly Cashman Series has effectively introduced computer skills to millions of students. With the Office 2007 Introductory Concepts and Techniques workbook students work through extra hands-on exercises reinforcing the skills taught in the text